Correlation between Risk Stratification of Complications and Types of Antihyperglycemia Drugs with Incidence of Acute Diabetic Complications in Patients with Diabetes Mellitus during Ramadan Fasting - Sasiarini, Laksmi; Simatupang, Charisma Dian; Arsana, Putu Moda (Universitas Brawijaya, 2020)
Ramadan fasting for Diabetes Mellitus (DM) patients can lead to acute complications such as hypoglycemia, hyperglycemia, diabetic ketoacidosis (DKA) and thrombosis. Risk stratification predicts fasting safety of DM patients. Dose and timing of antihyperglycemia drugs adjusted during Ramadan fasting. Aim: To know the correlation between the risk stratification of Ramadan fasting and type of antihyperglycemia drugs with the incidence of acute complications in DM patients undergoing Ramadan fasting. Methods: DM patients in Endocrinology Clinic, dr. Saiful Anwar, General Hospital Malang who intend to fast during Ramadan classified in IDF-DAR risk stratification, conduct blood glucose monitoring and filled out a daily logbook during fasting. Results: Thirty-seven subjects were included in the study, only 1 patient with type-1 DM. Average fasting time is 18 days. Acute complications found higher in very high-risk group (5/6) compared to mild/moderate (2/13) and high-risk group (7/18) (p=0.009). Acute complications found higher in group with OAD and insulin combination regiment (2/4) compared to OAD (9/24) or insulin group (3/9) (p= 0. 731). One subject in very high-risk group suffered from acute coronary syndrome. Relationship between risk stratification and the incidence of hypoglycemia (p=0.040) and hyperglycemia (p=0.031) was significant. Relative risk in the very high-risk group was 2.538 compared to mild/moderate risk RR (95% CI)= 0.77 (0.62-0.96). Conclusions: There is a correlations between risk stratification and acute complications in DM patients undergoing Ramadan fasting. No relationship between type of antihyperglycemia drugs with acute complications of Ramadan fasting.